Letter - Elger, William
042-0096-001 SCOTTISH TRADES UNION CONGRESS GENERAL COUNCIL 33 ELMBANK CRESCENT. WILLIAM ELGER, J.P. SECRETARY. PHONE: CENTRAL 3179 33 ELMBANK CRESCENT, GLASGOW. October 15th. 1937. Sir Walter M.Citrine, K.B.E., General Secretary, The Trades Union Congress, Transport House, London, S.W.1. Dear Sir Walter, Scottish Ambulance Unit Thanks very much for yours of the 13th inst., enclosing a copy of a letter of the same date which you have sent to Sir D.M. Stevenson from which I am glad to note that a final grant is being made to the Unit. Yours truly William Elger Secretary. 292/946/42/96